Enhancing The Understanding of Villagers in Semoyo Patuk Gunungkidul Yogyakarta Regarding Medicinal Chemical in Commercial Natural Products - Hadning, Ingenida; Widayati, Aris (LPPM Universitas Bumigora, 2025)
The consumption of herbal medicine in Indonesia has attracted people since ancient times. The trend of consuming jamu is increasing along with the COVID-19 pandemic. Some studies mention that medicinal chemical ingredients are added to marketed natural medicines for a specific purpose, that is not allowed. These medicinal chemicals are known to cause side effects that are very harmful to the body. This reported program aims to improve knowledge regarding the dangers of medicinal chemicals added in marketed natural products. The participants of this program were 30 members of Argomoyo Sejahtera inSemoyo Village, Patuk, Gunung Kidul, Yogyakarta. This program was held on Saturday, May 4th, 2024, at Universitas Muhammadiyah Yogyakarta (UMY). This program was carried out through education about medicinal chemicals added in marketed natural products. Participants were given a questionnaire before and after the education to evaluate their knowledge regarding the delivered materials. Data of the pre and post test were analysed using paired sample t-test. The results show that there is a significant increase in participants' knowledge, with a p-value of 0.017 (<0.05). These results indicate that education could effectively enhance knowledge about medicinal chemicals' dangers which are added to marketed natural products.